Surau in the Past, School Now and Artificial Intelligence of the Future - Mursal, Irhas Fansuri; Wita, Gusmira (Proceeding International Conference on Malay Identity, 2023)
Reading about the massive phenomenon of digital world development can have a big influence on the world of education. This article examines the comparison of traditional surau education, current school developments and the future of Artificial Intelligence. Surau is a traditional educational institution that forms a character based on Islam. Today's schools have the same opportunity to develop themselves through technology platforms and need to be serious about digitizing education. Artificial Intelligence helps in a world of work that is practical and requires lower costs. But don't let humans become dependent on Artificial Intelligence so that they lose their existing basic abilities. Abstrak Membaca fenomena perkembangan dunia digital yang begitu massif bisa memberikan pengaruh besar terhadap dunia Pendidikan. Artikel ini mengupas perbandingan Pendidikan tradional surau, perkembangan sekolah kekinian dan masa depan Arifisial Intelegensia. Surau Lembaga Pendidikan tradisional membentuk karakter yang berlandaskan Islam. Sekolah Hari ini guru punya kesempatan yang sama dalam mengembangkan diri lewat Platform Teknologi dan butuh keseriusan dalam digitalisasi Pendidikan. Artifisial Intelegensia membantu dalam dunia kerja yang serba praktis dan memerlukan biaya yang lebih murah. Tetapi jangan sampai manusia menjadi ketergantungkan dengan Artifisial Intelegensia sehingga  kehilangan kemampuan dasar yang sudah ada.